Framework for analyzing conceptions of excellence in higher education: a reflective tool. Issue 5 (29th July 2022) - de Jong, N. A.; Boon, M.; van Gorp, B.; Büttner, S. A.; Kamans, E.; Wolfensberger, M. V. C.
ABSTRACT: Honors programs and similar initiatives aimed at evoking excellence of students are increasingly promoted in higher education. However, there is a lack of conceptual clarity with regard to the concept of 'student excellence'. The purpose of this article is to present a conceptual framework, called FACE ( Framework for Analyzing Conceptions of Excellence ), which provides a reflective tool for analyzing ideas on who is excellent, what is student excellence, why is student excellence important, and how is excellence taught. The content of FACE is based on literature on giftedness, motivation and excellence in higher education. FACE consists of a horizontal axis with inclusive and exclusive views at the extremes, and vertically distinguishes between possible answers to the 'who'-, 'what'-, 'why'- and 'how'-questions. FACE as a reflective tool can facilitate constructive debate among teachers that work together to develop educational programs aimed at evoking excellence of students.